Sequence-specific (1)H, (13)C and (15)N assignments of the phosphoesterase (PE) domain of Pseudomonas aeruginosa DNA ligase D (LigD) - Dutta, Kaushik (2011)
DNA ligase D (LigD), consisting of polymerase, ligase and phosphoesterase domains, is the essential catalyst of the bacterial non-homologous end-joining pathway of DNA double-strand break repair. The phosphoesterase (PE) module performs manganese-dependent 3’-phosphomonoesterase and 3’-ribonucleoside resection reactions that heal broken ends in preparation for sealing. LigD PE exemplifies a structurally and mechanistically unique class of DNA end-processing enzymes. Here, we present the resonance assignments of the PE domain of Pseudomonas aeruginosa LigD comprising the N-terminal 177 residues.